(3GdOQQ GdefKhQIs - (3YHO Gddg Hf eMeO QVG THQ GdMSjfj GdcGXej,J (B1242 (3g` s ((3gGOj THQ GdMSjfj s)
(3ChdgG (B:s
(3GdbdhH Jed ceG Jed GdCHOGf aGHJZhG dgG XQGFa GdMceI hbGd(B: (3QhMhG GdbdhH hGHJZhG dgG XQGFa GdMceI aEfgG Jed ceG Jed GdCHOGf s
(3BNQgG (B:s
(3aGdJLCJ GdfaS Edi MUf GdeOjfI aCMGWhG HgG hfGRdhgG hMGUQhgG hVGjbhgG aYfO Pdc ONdJ aj GdWGYI hGdJSdje hfRdJ Ydj GdQZe Ydi Mce GdYRjR GdMcje s
(3fSNI Yf fSNI SbjeI aj ZGjI GdJThjT ef MjK GdSbW h GdZdW h GdRjGOI hGdfbUGfs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B6 s
Keywords: (3GdCOHs